Azathioprine induce hyperimmunoglobulin syndrome - Kandukuri, Durga mounika; Kumar, C Rakesh; Jyoshna, Somasani (Indian Journal of Case Reports, 2026)
This case was reported on the adverse effect of azathioprine drug toxicity and the importance of early recognition of the signs and symptoms of azathioprine toxicity. This case report involves a 60-year-old female patient who took excessive intake of tablet azathioprine for more than 6 months. The patient was diagnosed with hyperimmunoglobulin syndrome (HIES). Azathioprine is commonly used in the treatment of severe atopic dermatitis by suppressing immune responses and reducing inflammation, itching, and rashes. However, its immunosuppressive action may predispose patients to rare disorders. Hyperimmunoglobulin E (IgE) HIES is a rare primary immunodeficiency characterized by elevated IgE levels, recurrent skin infections, and eczema-like symptoms. This report presents a rare case of HIES in a 60-year old female with a history of hypertension, diabetes mellitus, and asthma, associated with prolonged azathioprine use. Clinical features, laboratory findings, and treatment regimens are discussed.